2020
DOI: 10.1136/bmjopen-2020-041921
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the UCLA 3-item loneliness scale for community-based depressive symptoms screening interview among older Chinese: a cross-sectional study

Abstract: ObjectiveLoneliness is a significant and independent risk factor for depression in later life. Particularly in Asian culture, older people may find it less stigmatising to express loneliness than depression. This study aimed to adapt a simple loneliness screen for use in older Chinese, and to ascertain its relevance in detecting depressive symptoms as a community screening tool.Design, setting and participantsThis cross-sectional study was conducted among 1653 older adults aged 60 years or above living in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 55 publications
8
52
0
Order By: Relevance
“…Statistically, a cut-off score of 5 on the scale (ranging from 3 to 9) was supported by the ROC curve analyses. This is similar to the findings of a recent study among older adults [7], which showed that a cut-off of 3 (on a scale from 0 to 9) using a modified Cantonese translation of the UCLA Scale showed good accuracy at classifying cases of depression. However, the trade-off between sensitivity and specificity can be informed by other priorities besides accuracy alone, such as the cost of committing a false negative versus a false positive [28].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Statistically, a cut-off score of 5 on the scale (ranging from 3 to 9) was supported by the ROC curve analyses. This is similar to the findings of a recent study among older adults [7], which showed that a cut-off of 3 (on a scale from 0 to 9) using a modified Cantonese translation of the UCLA Scale showed good accuracy at classifying cases of depression. However, the trade-off between sensitivity and specificity can be informed by other priorities besides accuracy alone, such as the cost of committing a false negative versus a false positive [28].…”
Section: Discussionsupporting
confidence: 90%
“…Societal perceptions of loneliness and mental health problems may differ across cultural contexts, and hence the association between these phenomena may similarly vary in strength or be mediated by different processes. The study by Liu and colleagues [7] found similar results to the present study in a sample of older Hong Kong residents; however, further research is merited to attempt replication in other populations. Furthermore, while the findings were replicated in two different age brackets, it is unclear to what extent they hold true in older age, when the experience of loneliness and the reasons for it may differ from earlier stages of the lifespan.…”
Section: Strengths and Limitationssupporting
confidence: 81%
See 2 more Smart Citations
“…Social support was measured using the 3-item Oslo Social Support Scale (OSSS-3) and sum scores were operationalized into three categories: poor support (3-8), moderate support (9)(10)(11), and strong support (12-14) (33). Loneliness was measured using an adapted version of the UCLA 3-item Loneliness scale with a four-point Likert scale ("never, " "once in a while, " "fairly often, " and "very often"), yielding a score from 0 to 9 (34,35). Respondents with a score ≥6 were categorized as experiencing a high level of loneliness.…”
Section: Predictor Variablesmentioning
confidence: 99%